Effect of Salinity Stress on Oxidative Stress Parameters and the Activity of Antioxidant Enzymes in Eight Durum Wheat Genotypes - AL-Hamood, Mohammad; AL-Ouda, Ayman Shehada; AL-Bisky, Fahed (Iraqi Journal of Science, 2023)
This study was carried out at the Tissue Culture Laboratory, which belongs to the General Commission of Biotechnology, in order to evaluate the influence of NaCl-induced salinity stress on some oxidative parameters (MDA and H2O2) and antioxidant enzymes (CAT, APX, and SOD) in eight durum wheat genotypes (Doma1, Bouhoth11, Cham3, Bezater, Cham5, Aghamatales, Icaverve, and Icamber) in vitro, to determine the most salinity tolerant genotypes. Salinity stress was applied by adding different levels of NaCl to the growing medium (0, 50, 100, and 150 mM). The experiment was laid according to a complete randomized design (CRD) with sixteen replicates. Increasing salinity level caused an increase in both the Hydrogen peroxide (H2O2), malondialdehyde (MDA) and the activity of the investigated antioxidant enzymes (SOD، APX، CAT) compared with the control. The leaf content of both H2O2 and MDA was significantly higher in the genotype Icaverve at the salinity level of 150 mM NaCl (45.67 and 130.74 µmol g-1 fresh wt. respectively), while the activity of the enzymes SOD, APX and CAT were significantly higher in the two durum wheat genotypes, Bouhoth11 and Doma1 at the highest salinity level (150 mM NaCl). Antioxidant enzymes play a pivotal role in the defense mechanisms in the durum wheat under salinity stress conditions, and the in vitro screening tool can be effectively used to assess the genetic variability for salinity tolerance in the durum wheat crop.